Implementasi Metode Talking Stick Berbantuan Kertas Origami Untuk Meningkatkan Hasil Belajar Siswa - Faustina, Farah Nur; Fahyuni, Eni Fariyatul (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
Good cooperation must be carried out by teachers and students in achieving the educational goals stated in the National Education Law. There are still various kinds of problems in the world of education, including in improving student learning outcomes during the learning process. This research is quantitative research with experimental methods. The research was conducted in two classes, namely class V-B as the control class and class V-A as the experimental class. Based on the results of the study, it was found that the Talking Stick learning method had a significant effect on student learning outcomes. This is based on the acquisition of the average value of experimental class students higher than the average value of the control class. In addition, the results of hypothesis testing that have been carried out also show a significance value of 0.001 <0.05, so it can be concluded that there is an increase in student learning outcomes in class V-A when given the Talking Stick learning method. In addition, student learning outcomes after participating in learning using the Talking Stick method and conventional learning have a significant difference as evidenced by the significance value of 0.002 < 0.05.